А source study analysis of Amir Timur’s waquf diploma issued by the Turkestan mosque of Khoja Ahmet Yasavi at the end of the XIV- the beginning of the XV century - Kumekov, Bulat; Kartova, Zaure (Turkic Studies Journal, 2021)
The article is devoted to a source study of the form of the waquf certificate issued by Amir Timur of the Turkestan mosque of Khoja Ahmet Yasavi in the late XIV - early XV centuries. This is one of the earliest documents related to the socio-economic history of the cities of southern Kazakhstan. For a long time, the letter was considered a fake document. At the same time, the analysis of the form and steady turnovers applied to medieval acts of sources makes it possible to question the falsity of this document. It is determined that the conditional form of the waqfic literacy corresponds to all the structural components of medieval labels that were widely used in the chancellery of the Golden Horde and post-Golden Horde states. It should be taken into account that the publication of the waqfic diploma issued by Amir Timur to the Turkestan mosque of Khoja Ahmet Yasavi at the end of the XIV - beginning of the XV centuries is of great importance for historical science. The source can be used in scientific research as the most important autochthonous and authentic source of the Middle Ages.